Säänneltyä joustavuuutta: Hankemekanismit kansainvälisessä ilmastopolitiikassa - Heikki Marjosola (The Research Institute of the Finnish Economy (ETLA), 2008)
Kyoto Protocol's Project-Based Mechanisms (Clean Development Mechanism, CDM and Joint Implementation, JI) add flexibility to international climate cooperation and emission trading schemes. The mechanisms reduce the costs of achieving the emission targets directly (cheaper implementation of the emissions reducing projects abroad) and indirectly (emission units earned increase the liquidity of the markets). While the carbon market has been running, some of the problems of the project-based markets have transpired. The CDM projects have centered largely on the biggest and richest developing countries, which also pollute a lot. The smaller developing countries that are more unstable and do not have as developed institutional capacity, are not as intriguing for risk-averting international capital. Though many developing countries are hosting CDM-projects, the centering of the market seems to feed itself. The reforms of the CDM market regulation try to decelerate this tendency (for example programmatic CDM, and new financing mechanisms). Industrialized countries also try to persuade the biggest developing countries to accept an emission target. Thereby they would no longer compete with developing countries, but with industrialized countries likely to host JI-projects. The development of the EU ETS is important from the point of view of project-based markets. In the future, the EU ETS will be governed more as a federate system under harmonized rules. The underlying problem of the international system, however, is the artificial dichotomy of the world into industrialized and developing countries. In the Emissions Trading Schemes, the different developing stages of the countries, regions and industrial operators can be considered much more efficiently. Linking of the already existing schemes provides a necessary step towards a more global and comprehensive Emissions Trading Scheme.
Keywords: 330; Project-based mechanisms; CDM; JI; flexibility; Emissions Trading Schemes; linking